2015
DOI: 10.12669/pjms.316.7047
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and determinants of Hepatitis B and C virusin general population of Farash Town, Islamabad

Abstract: Background and Objective:Both Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are rapidly spreading in the developing countries. Both of them are blood borne and are transmitted through un-screened blood transfusion, inadequately sterilized needles and equipment. According to WHO’s criteria of endemicity, Pakistan has high disease burden of Hepatitis B and C. The present study was planned to determine the frequency and to identify the risk factors of hepatitis B and C virus in the general commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…[ 16 ] Another risk factor that was identified in our study was the history of surgery which is also in agreement with other studies conducted in Pakistan. [ 17 ] Family history with HCV is one of the significant factors on our side which is similar to another study which concludes that there are 2.5 times greater chances of being positive if you have a positive family history as compared to the general population. [ 18 ] Considering this, it is recommended that active screening of the families of HCV infected patients be done routinely.…”
Section: Discussionsupporting
confidence: 74%
“…[ 16 ] Another risk factor that was identified in our study was the history of surgery which is also in agreement with other studies conducted in Pakistan. [ 17 ] Family history with HCV is one of the significant factors on our side which is similar to another study which concludes that there are 2.5 times greater chances of being positive if you have a positive family history as compared to the general population. [ 18 ] Considering this, it is recommended that active screening of the families of HCV infected patients be done routinely.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies and investigators reported a lower prevalence of HBV infections than our observation. In a previous study, it was reported that the prevalence of HBsAg seropositivity among a population of 345 tested cases was relatively lower [13]. In the current study, blood transfusion was considered as an important were higher among males (62.26%) when compared with females (37.74%).…”
Section: Discussionmentioning
confidence: 43%
“…HIV, HBV and HCV infections are a serious health burden in Pakistan. [11][12][13][14] Diagnosis and point of care strategies require thorough understanding of infection's severity in the Pakistani population. Elevated CF mt-DNA levels have been observed in different pathophysiological conditions.…”
Section: Discussionmentioning
confidence: 99%